(untitled) (Revista Logos Ciencia & Tecnología, 2019)
The objective of this study was to evaluate the removal efficiency of a filter system using flotation macrophytes on a laboratory scale using water from a car wash. The Water Hyacinth (Eichhornia crassipes) and duckweed (Lemna minor) were use in the system, and the concentrations of BOD5, COD, TSS and SS in the system effluent were monitor for one month. Regarding the reduction of the parameters analyzed using Water Hyacinth, there was a maximum of 91.11% BOD5 removal and 97.32% COD, in the case of Duckweed 97% BOD5 removal and 83.67% COD. Finally, the system demonstrated optimum performance and removal efficiencies of more than 44.4% in terms of organic matter, sedimentary solids and suspended solids.